Gamification and Classroom Management in a Group of Fifth Graders (2023)
ABSTRACT: This project was developed with fifth-year students of the Fe y Alegria Luis Amigó Educational Institution. Due to the behaviour of the students in class, where there is evidence of inattention and disorder during classes, we decided to carry out an action research study in order to implement different recreational activities based on gamification. With this we want to improve student restless habits during English class and have an adequate classroom management that contributes in a better way to the learning of the language. To do this, we identified the problem, implemented the proposed actions and, finally, carried out an analysis based on the following sources of information: field diaries (journals), a questionnaire for the cooperating teacher in charge of the group, and an interview with a target group of students. After this analysis, we identified favourable results that demonstrated the positive influence of gamification in the English class to improve classroom management.